Implementation of Credit Restructuring on Agreements Based on the Principles of Contract Law - Tahir, Muhammad Auzan (Dinasti Publisher, 2025)
This study aims to analyze the implementation of credit restructuring based on the principles of contract law in Indonesia, particularly in the context of economic instability that affects the ability of debtors to fulfill their obligations. Through a doctrinal and normative legal approach, this study examines the restructuring policies implemented by financial institutions by reviewing relevant regulations, legal principles, and their practical implementation. This study finds that although credit restructuring is clearly regulated in regulations such as the “Otoritas Jasa Keuangan” (OJK) Regulation, there are challenges in its implementation related to the principles of freedom of contract, equilibrium, and morality, especially when creditors refuse to grant restructuring even though debtors meet the criteria. This study suggests the need for more equitable and flexible policies, as well as improved understanding among debtors of their rights and obligations under credit agreements. The findings of this study are expected to contribute to the development of more efficient and fair credit restructuring policies for both parties, as well as maintaining the stability of the banking sector in Indonesia.